2019
DOI: 10.5194/os-15-717-2019
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: On the importance of a three-dimensional approach for modelling the transport of neustic microplastics

Abstract: Understanding and estimating the distribution and transport of microplastics in marine environments has been recognized as a major global research issue. Most of the existing research on transport modelling has focused on lowdensity particles floating in surface waters, using a 2-D Lagrangian approach and ignoring the vertical displacement of particles. In this work, we evaluate to what extent the vertical movement of particles within surface waters by mixing processes may affect the horizontal transport and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…They serve as a primary mode of carbon export out of the exogenic carbon pool and deliver sediment to the world ocean floor: An important archive for understanding the climate system. The lateral advection of the sinking particles by ocean currents complicates the estimation of downward particle fluxes captured by sediment traps [ 1 ], the paleoceanographic reconstructions based on sedimentary microplankton distributions [ 2 – 5 ], and the estimation of micro-plastic distributions in the ocean [ 6 ]. Initially buoyant micro-plastic in the ocean sinks when it gets biofouled and its density increases [ 7 ], meaning that a large fraction of the plastic in the ocean has already sunk to the ocean floor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They serve as a primary mode of carbon export out of the exogenic carbon pool and deliver sediment to the world ocean floor: An important archive for understanding the climate system. The lateral advection of the sinking particles by ocean currents complicates the estimation of downward particle fluxes captured by sediment traps [ 1 ], the paleoceanographic reconstructions based on sedimentary microplankton distributions [ 2 – 5 ], and the estimation of micro-plastic distributions in the ocean [ 6 ]. Initially buoyant micro-plastic in the ocean sinks when it gets biofouled and its density increases [ 7 ], meaning that a large fraction of the plastic in the ocean has already sunk to the ocean floor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the water compartment, experimental and numerical approaches are generally limited to floating microplastics, such as surface sampling and 2D Lagrangian particle-tracking models coupled with ocean circulation models (Isobe et al, 2009;Kako et al, 2010;Lebreton et al, 2012;Murray et al, 2018;Neumann et al, 2014;Sherman and Van Sebille, 2016), assuming that most of the microplastics load is floating (Mani et al, 2015;McCormick et al, 2016;Yonkos et al, 2014), and focusing on the longitudinal spread of the plastics load from cities and sewage plants (Dris et al, the open ocean where most heavy particles would have sunk well beyond the resuspension (closure) depth. However, the vertical structure of the plastics load can certainly not be ignored in coastal and estuarine environments where the hydrodynamics is generally able to maintain in suspension sediments which are heavier than typical polymers (Forsberg et al, 2020;Jalón-Rojas et al, 2019;Kukulka et al, 2012). To numerically study the dispersion of microplastics in areas of intense turbulence or wave mixing, it was shown that vertical turbulence model and particle inertia are key parameters (Jalón-Rojas et al, 2019;Stocchino et al, 2019;DiBenedetto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a perfect match between sea water and plastic debris density inhibits any physical mechanism of sedimentation, which is indeed neglected when assuming neutrally buoyant particles. On the contrary, other approaches allowed to consider a settling velocity disregarding any drag-induced effect, both in a lagrangian [14,19] and in an eulerian [20] approach; the settling velocity of the particles was also taken into account in Liubartseva et al [17], who simulated the sedimentation of particles through a statistical approach based on Montecarlo simulations. Nevertheless, it has to be pointed out that the drag may be reasonably neglected only for some regimes of the controlling parameters, i.e., Froude and Stokes number.…”
Section: Introductionmentioning
confidence: 99%